THE IMPACT OF COVID-19, TRADING VOLUME ACTIVITY AND MARKET CAPITALIZATION ON STOCK RETURN OF LQ-45 COMPANIES - Chandra, Nadya Aurelia; Suhendah, Rousilita (Graduate Program of Universitas Tarumanagara, 2023)
The objective of this research is to analyze the impact of daily growth of Covid-19 positive case, Trading Volume Activity (TVA), and market capitalization on LQ-45 companies’ stock return in IDX on the year 2020. This research uses multiple regression models on sample size of 41 companies using non-probability sampling method. This research’s analysis approach is as follow: statistical descriptive analysis, t-test, F-test and Coefficient of Determination test. Data processing in this research is done by Microsoft Excel and Eviews 12. This study uses Signalling Theory, Black Swan Theory and Efficient Market Hypothesis Theory as grand theories to explain the relationship between variables used in this study and resulted that the daily growth of Covid-19 positive case and TVA partially have a positive effect on stock return, while market capitalization has a negative effect on stock return. This research is designed to be beneficial for investors as a basis for making investment decisions, as well as assisting company management regarding the management of company performance to increase stock prices.